Pengaruh Ukuran Kap, Opini Audit dan Pergantian Manajemen terhadap Auditor Switching (Studi Pada Perusahaan Bumn yang Terdaftar di Bursa Efek Indonesia) - Sufiati (Insan Cita Bongaya Research Journal, 2021)
This study aims to determine whether the size of KAP, audit opinion and management turnover have an effect on auditor turnover in state-owned companies listed on the Indonesia Stock Exchange. Data collection uses secondary data obtained from the STIEM Bongaya Investment Gallery. The population is state-owned companies listed on the Stock Exchange, totaling 26 companies, while the sample taken is 19 companies, with the observation method for 4 years, the total companies observed are 76 companies. The sampling technique used purposive sampling method and the data results were processed using logistic regression analysis method with the help of SPSS 26 software.The results show that partially only audit opinion has an effect on auditor switching, while the size of KAP and management change has no effect on auditor switching. Keywords: KAP Size, Audit Opinion, Management Change, Auditor Change